1994
DOI: 10.1042/bj3000583
|View full text |Cite
|
Sign up to set email alerts
|

Expression of liver carnitine palmitoyltransferase I and II genes during development in the rat

Abstract: The enzyme activity and the expression (protein and mRNA concentrations) of genes encoding for hepatic carnitine palmitoyl-transferases (CPT) I and II were studied during neonatal development, in response to nutritional state at weaning and during the fed-starved transition in adult rats. The activity, the protein concentration and the level of mRNA encoding CPT I are low in foetal-rat liver and increase 5-fold during the first day of extra-uterine life. The activity and gene expression of CPT I are high durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 49 publications
9
67
0
2
Order By: Relevance
“…Incubation of cultured foetal rabbit hepatocytes with long-chain fatty acids also induces the expression of CPT I [64]. Similarly, studies on neonatal-rat liver have shown that the increase in insulin\glucagon concentration ratio that accompanies weaning of the pups on to a highcarbohydrate diet is accompanied by a rapid decline in the CPT I mRNA content, but not in that of CPT II [65]. Interestingly, the expression of CPT I protein showed a much more gradual decline than that of its mRNA, indicating that the protein has a long half-life.…”
Section: Enzymes Involved In the Partitioning Of Fatty Acids Between mentioning
confidence: 93%
“…Incubation of cultured foetal rabbit hepatocytes with long-chain fatty acids also induces the expression of CPT I [64]. Similarly, studies on neonatal-rat liver have shown that the increase in insulin\glucagon concentration ratio that accompanies weaning of the pups on to a highcarbohydrate diet is accompanied by a rapid decline in the CPT I mRNA content, but not in that of CPT II [65]. Interestingly, the expression of CPT I protein showed a much more gradual decline than that of its mRNA, indicating that the protein has a long half-life.…”
Section: Enzymes Involved In the Partitioning Of Fatty Acids Between mentioning
confidence: 93%
“…The human CPT II promoter contains a TATA box [14] but the mouse gene has no TATA box [13]. However, it would be anticipated that the promoters of the L-CPT I and CPT II genes should be different since the CPT II gene is expressed in all tissues and is not subject to hormonal or developmental control [18,20]. The human M-CPT I promoter also appears to be different as it utilizes two alternatively expressed first exons [10].…”
Section: Analysis Of the Sequence In L-cpt I Promoter Regionmentioning
confidence: 99%
“…There is considerable evidence for the presence of additional CPT activities in peroxisomes and microsomes based upon cDNA cloning, protein purification and antibody studies [15][16][17]. L-CPT I gene expression and enzyme activity increase dramatically in the liver at birth [18]. With weaning to a high fat diet, transcription of L-CPT I remains high while weaning to a high carbohydrate diet results in diminished L-CPT I expression [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations